Limited infection with occult hepatitis B virus in drug users in the USA. Issue 4 (22nd August 2012) - Blackard, Jason T.; Martin, Christina M.; Sengupta, Satarupa; Forrester, Janet
<x xml:space="preserve">Abstract</x> Aim: Occult HBV infection (O‐HBV) is defined as low level HBV replication in the absence of detectable circulating HBV surface antigen. O‐HBV has been implicated in HBV reactivation, advanced liver fibrosis and cirrhosis, reduced interferon response rates, elevated liver enzyme levels, and the development of hepatocellular carcinoma. However, the prevalence of O‐HBV has not been clearly established in certain at‐risk populations, such as injection drug users. Methods: Therefore, the current pilot study examined the prevalence of O‐HBV in a prospective cohort designed to assess the role of injection and non‐injection drug use (IDU) on HIV‐associated comorbidities. Results: Utilizing two distinct real‐time polymerase chain reaction assays, HBV DNA was not detected in 99 participants examined. Conclusion: This finding is in contrast to other data from US IDU cohorts and suggests that the prevalence of O‐HBV infection is very specific to the cohort studied, is sensitive to other confounding variables such as hepatitis C virus and/or HIV serostatus, and should not be generalized across risk groups or distinct cohorts.